(untitled) (Research, Society and Development, 2020)
Objective: The present study aims to analyze in the productions available, the effect of visual stimulation in children with Down syndrome. Methodology: It is a systematic review of qualitative nature, which used the following databases for the search: Pub Med, Capes periodic portal, SciELO and Google Scholar; using the following descriptors "Children", "Down syndrome", "low vision" and "luminous stimulation, studies were selected in Portuguese and English; in the period of 2010-2020; the search itself occurred in the month of August 2020; for the construction of the research question the strategy was used PICO (population, intervention, comparison and outcome). Results: From the 8 articles selected for the study of this publication, it was possible to analyze the main ophthalmological changes that affect children with Down syndrome, among these are: refraction errors, strabismus, nystagmar and blepharitis. In this context, early diagnosis was necessary for the identification of these disorders and makes it impossible for these changes to be maximized over the years. In the articles survey also showed that luminous stimulation prevents the various complications arising and reduces these visual disorders. Conclusion: The luminous stimulation, in parallel, with the identification of the early diagnosis, acts as a resource that allows these children to bear down syndrome they can develop an improvement in visual function, thus promoting benefits that can improve the quality of life of this child.